Robotic Training to Bridge School Students with Engineering - Balaji, M. (Elsevier B.V., 2015)
Engineers play a vital role in the growth of every country and creating productive engineers has become top priority for the policy makers. So, efforts are put into place to produce engineers right from school education in almost all places. In this paper, we present robotics as the tool to create awareness on engineering in the minds of school students before they get ready to choose their career. The robotic trainer, FASTBot is the ideal platform enabling school students understand various elements like science, technology, mathematics and apply their knowledge in these areas effectively with additional inputs like programming, logical analysis to create solutions for the given task. They get insights into robotic components like embedded systems, sensors, mechatronics and related knowledge. Students can distinguish mediocre results from the exact and required results and then start working for the desired results in their robotic interactions. We proceed to describe how this bot is equipped with more facilities to help the students get better understanding on the aspects of engineering when they get ready to take up first major step in their career. Â© 2015 The Authors.